2012
DOI: 10.1088/0953-4075/45/21/215602
|View full text |Cite
|
Sign up to set email alerts
|

Non-dipole effects in the angular distribution of photoelectrons in sequential two-photon atomic double ionization

Abstract: Abstract. Motivated by the recent achievements of experiments using X-ray free electron lasers, we develop a theory for the angular distributions of photoelectrons in sequential two-photon double ionization (2PDI) of atoms beyond the dipole approximation. Expressions for the angular distributions are obtained taking into account the full multipole expansion of radiation in electric and magnetic moments. The formalism is further specified for the first-order corrections to the dipole approximation. As illustrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 47 publications
(132 reference statements)
2
33
0
Order By: Relevance
“…To confirm our findings and to improve quantitative significance, further measurements at a number of photon energies in the Cooper minimum region are necessary. The role of Cooper minima for sequential ionization processes and its impact on the angular distributions of all involved steps is especially important with respect to a breakdown of the dipole approximation in the non-linear regime [39]. A future investigation of this kind can benefit from the recent prosperity in FEL evolution, especially in terms of wavelength tunabilty.…”
Section: Conclusion (And Outlook)mentioning
confidence: 99%
“…To confirm our findings and to improve quantitative significance, further measurements at a number of photon energies in the Cooper minimum region are necessary. The role of Cooper minima for sequential ionization processes and its impact on the angular distributions of all involved steps is especially important with respect to a breakdown of the dipole approximation in the non-linear regime [39]. A future investigation of this kind can benefit from the recent prosperity in FEL evolution, especially in terms of wavelength tunabilty.…”
Section: Conclusion (And Outlook)mentioning
confidence: 99%
“…Recent calculations [28,58,59] for the sequential 2PDI in Ne, Ar, and Kr showed that at the photon energies starting from about 1 keV and at lower energies in the region of the Cooper minima, the nondipole corrections could be important for the PADs. General formalism was developed in [59] for the PADs and the angular correlation functions between the emitted electrons for arbitrary polarized photons and taking into account the full multipole expansion of radiation in electric and magnetic moments.…”
Section: Nondipole Effects In Sequential 2pdimentioning
confidence: 99%
“…General formalism was developed in [59] for the PADs and the angular correlation functions between the emitted electrons for arbitrary polarized photons and taking into account the full multipole expansion of radiation in electric and magnetic moments. The development is based, similar as in the dipole approximation, on the stepwise model of the sequential 2PDI and the formalism of statistical tensors.…”
Section: Nondipole Effects In Sequential 2pdimentioning
confidence: 99%
See 2 more Smart Citations